Pengaruh Pupuk Hayati Berbasis Azolla terhadap Nitrogen Tanah, Nitrogen Tanaman, Populasi Azotobacter, dan Hasil Tanaman Mentimun Pada Inceptisol Jatinangor - Mieke Rochimi Setiawati; Evi Entang Fatimah; Diyan Herdiyantoro; Apong Sandrawati; Uum Umiyati; Pujawati Suryatmana (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2022)
The low productivity of cucumber plants in Indonesia can be caused by several factors, one of which is fertilization. Fertilization on Inceptisol soil which has a low nitrogen content is needed to increase cucumber crop yields. The use of inorganic fertilizers is limited to avoid environmental pollution, so the use of biofertilizers can be an environmentally friendly option. The purpose of this study was to determine the effect of concentration and interval application of azolla extract based biofertilizer on the total soil N, plant N content, Azotobacter population and cucumber yield. The experiment was carried out from August to November 2021 at the Ciparanje Experimental Garden, Faculty of Agriculture, Padjadjaran University. This experiment used a Completely Randomized Block Design of a combination concentrations (0, 5, 10, 15, 20 mL.L-1) and time of application (1, 2, 3 times). The results showed that the application of azolla extract based biofertilizer with different concentrations and application times had a significant effect on the azotobacter population but had no significant effect on soil nitrogen levels, plant nitrogen concentrations, and cucumber yields. The addition of 20 mL/L 2 times application of azolla-based biofertilizer increased cucumber fruit weight by 35.97% compared to control but did not cause a significant increase in yield